SOSIALISASI PEMANFAATAN APLIKASI “BUSA ONLINE” PADA PENGEPUL SAMPAH DI KECAMATAN WONOAYU KABUPATEN SIDOARJO - Wahyu Eko Pujianto; Supriyadi Supriyadi; Muhafidhah Novie (Mafaza : Jurnal Pengabdian Masyarakat, 2023)
Garbage has been a problem that needs the attention of every people. Economic growth has resulted in many activities and human consumption resulting in increased production of household waste. In addition, many people are littering, it a lack of knowledge about waste management. Technology development current can be a solution to trouble the dump management system, where most of the garbage collectors and people could enjoy the application busa online e-Recycle to facilitate garbage collector in the sorting of garbage can recycle. the implementation of this devotion used the Participatory Action Research (PAR). PAR aimed to provide alternative solutions to solving a problem going that was going on. PAR has four stages observation, planning, action and evaluation. The result of this devotion. Socialization got a positive response from the community especially the garbage collector so the activities were carried out running smoothly. Participants use the application busa online Capable of understanding the importance of the development of technology and environmental sustainability, Participants can also use the application busa online e-Recycle as a system which made it easier the sorting of waste with efficiency, So people are aware of the need to no longer littering